Understanding Tsetse Fly (Glossina morsitans) Behavior through its Genome - Marbun, Kristin Talia; Nugroho, Satya; Jo, Juandy (Fakultas Kedokteran Universitas Pelita Harapan, 2023)
Glossina morsitans (G. morsitans), commonly known as tsetse fly, have caused public health concerns throughout the years. G. morsitans is the vector for Trypanosoma brucei (T. brucei), the parasite responsible for causing the deadly African sleeping disease (African trypanosomiasis). Researchers have searched for ways to contain this disease, but to little avail. Fortunately, new advances in sequencing methods have given researchers a new opportunity to win the war against the disease. The whole-genome sequence of G. morsitans provides essential data regarding involved genes that transmits T. brucei to humans. Information about those unique genes facilitates researchers to create new methods to prevent G. morsitans from becoming the vector of T. brucei, enabling the containment of this disease. With this, we review the unique genes in the G. morsitans genome, such as those that contribute to blood-feeding ability, establish a relationship with symbionts, and G. morsitans unique sensory genes, with an expectation that it would enhance our knowledge of G. morsitans as the vector for parasites causing African trypanosomiasis.